PEMBUATAN ELEKTRODA SELEKTIF ION Cr (VI) DENGAN MENGGUNAKAN MEMBRAN KITOSAN - Agus Kembaren; Roita T.T Panggabean (Jurnal Pendidikan Kimia (JPKim), 2014)
Abstract This research was aimed to make and to determine analytical performance of  Cr (VI) ISE. The electrodes has made by mixing Chitosan(as electroactive), PVC (as matrix), and DBP (as plasticizer) in THF. Composition of PVC and DBP maintane in fix ratio, 1: 2, while the chitosan varried, 4%, 7%, 10%, 13% and 16%. The composite membrans soak into 1M K2Cr2O7 solution for the night, then tight on the tip of electrode body. Analytical performance of the electrodes were determined by nersnt factor and dynamic range, response time, selectifity coeficient, and life time. The results show that the electrodes with composition 4 % chitosan, 32 % DBP, and 64 % PVC have optimum performance. Dynamic range of this electrodes is between 10-5 M - 10-1 M , slope/nersnt factor 32.004 mv/decade, average response time 20.7 seconds. The electrodes are not interfered by  Mn2+, Zn2+ and Fe3+. The electrodes can used with good performance in 3 days. Kata kunci : Elektroda selektif ion, membran kitosan